Blepharoptosis correction transconjunctivally using buried suture method: A prospective cohort study. (January 2016) - Lee, Hyejeong; Lee, Munjae; Bae, Sangmo
Abstract: Background: Blepharoptosis correction with minimal eyelid scarring is a desirable outcome. The aim of this study was to describe in detail our method of blepharoptosis correction transconjunctivally using buried suture method and to demonstrate its effectiveness. Methods: From June 2012 to May 2013, we performed a blepharoptosis correction transconjunctivally using buried suture method on 458 eyelids in 245 patients. During this procedure, we utilized six separate threads to form multiple knots. This thread was transconjunctivally inserted into the point located above the superior tarsal margin involving the superior levator palpebral and Müller muscles. Results: A total of 409 eyelids (89%) were successfully corrected. Undercorrection was encountered in 49 eyelids (25 patients). Of the 25 patients, only 16 patients were dissatisfied with the undercorrection and thus underwent reoperation. Three patients with asymmetric double eyelid ptosis also underwent reoperation. Five patients required reoperation to correct eyelid fold loosening, which occurred during the follow-up period. No major complications such as overcorrection, persistent irritation, and keratitis were observed. Conclusions: Using our technique, we could achieve the desired correction by accurately checking the rate of correction. We have demonstrated here excellent predictability and success rate in mild and moderate ptosis. We believe that a blepharoptosis correction transconjunctivally using buried suture method is an effective treatment method. Highlights: Blepharoptosis correction without surgical eyelid scarring is a desirable outcome. We performed a non-incisional transconjunctival blepharoptosis correction on 458 eyelids in 245 patients. Using our technique, we could achieve the desired correction by accurately checking the rate of correction.